On optimal factor proportions in a competitive firm under factor and output price uncertainty - Ulrich Lächler (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1983)
Most observers of economic events have noticed a considerable increase in the general volatility of prices over the last decade. An important byproduct often attributed to this increased price variability is greater uncertainty perceived by individual decisionmakers in the process of formulating intertemporal plans. This paper seeks to clarify and provide some extensions to previous theoretical work on the question of how economic agents adjust to increased price uncertainty in the context of the competitive firm. In particular, the question asked is whether the optimal choice of inputs in a competitive firm is affected by the advent of increased factor and output price uncertainty. The answer given in earlier studies such as those by Baron (1970), Batra and Ullah (1974), Leland (1972) and Sandmo (1971) is quite straightforward: If competitive-firm managers are risk-neutral profit maximizers, the optimal input mix remains unaffected by increased uncertainty, while under risk-averse managers, firms either reduce their scale of operations or adjust their input mix towards relatively greater use of less risky inputs.
Keywords: 330